1998
DOI: 10.1111/j.1468-2885.1998.tb00223.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Structurational Model of Identification in the Organization

Abstract: In response to the growing interest in issues related to attachment in organizations, this paper develops a theory of identification in the workplace based on three key aspects of structuration theory. In this model, the identification process is treated as a duality involving identities that create and are created by identifications, which are themselves observed in social interactions with others. The structural component of this model is composed of several possible identities conceptualized primarily in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
362
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(387 citation statements)
references
References 93 publications
14
362
0
5
Order By: Relevance
“…The "heart" of identification lies in the cognition and value one places on membership (Ashforth et al, 2008, p. 328). Communicating one's identity-I am a part of this organization, and this organization is important to me-remains a key feature of identification (Scott et al, 1998). Data revealed conflicting identity narratives, in that some participants considered themselves part of the organization whereas others did not.…”
Section: Sources Of Learning and Adapting During Internshipsmentioning
confidence: 95%
See 1 more Smart Citation
“…The "heart" of identification lies in the cognition and value one places on membership (Ashforth et al, 2008, p. 328). Communicating one's identity-I am a part of this organization, and this organization is important to me-remains a key feature of identification (Scott et al, 1998). Data revealed conflicting identity narratives, in that some participants considered themselves part of the organization whereas others did not.…”
Section: Sources Of Learning and Adapting During Internshipsmentioning
confidence: 95%
“…Identification involves communication because identities develop through social interactions (Scott, Corman, & Cheney, 1998). For the most part, people benefit from a strong sense of identification, because when people identify, they feel more integrated at work than people who do not identify (Carmeli, Gilat, & Waldman, 2007).…”
Section: Organizational Identificationmentioning
confidence: 99%
“…Alanyazın taraması sonucu ulaşılan ölçekler ve araştırmalardan (Dutton ve Dukerich, 1991;Edwards ve Peccei, 2007;Edwards, 2005;Johnson, Johnson ve Heimberg, 1999;Melewar, 2003;Miller, Allen, Casey ve Johnson, 2000;Scott, Corman ve Cheney, 1998;Tüzün, 2006) …”
Section: öLçme Aracı Ve Verilerinin Toplanmasıunclassified
“…Alanyazında örgütsel kimliğin, öncülleri ve sonuçlarıyla farklı boyutlarıyla ele alındığı görülmektedir. Bu araştırmaların bazıları şunlardır; Scott, Corman ve Cheney (1998) ;Meyer, Becker ve Van Dick (2006) ;Cheney ve Tompkins (1987) örgütsel kimlik algısı ile örgütsel adanmışlık ilişkisi ;Rotondi, (1975) örgütsel kimlik ve gruba katılım ilişkisi; Lee, (1969) bilim insanlarının örgütsel kimlik algısının belirlenmesi; Larson ve Pepper, (2003) örgütsel kimlik stratejilerinin tespiti ;Garmon, (2004) örgütsel kimlik ile kimlik, imaj, kültür ve örgütsel öğrenme arasındaki ilişki; Foote (1951) örgütsel kimlik ve motivasyon arasındaki ilişki ;Cherim, (2002) ise örgütsel kimlik ve örgütsel değişim stratejileri arasındaki ilişki boyutlarında konuyu ele aldıkları çalışmalardır. Türkiye'deki ilgili alanyazın tarandığında, konuyla ilgili yeni ve az da olsa bazı çalışmaların olduğu görülmektedir (Okay, 2000;Ertürk, 2003;Tüzün, 2006;Taşdan, 2010).…”
unclassified
“…Studies conducted over the past three decades (Ashforth & Mael, 1989;Foremen & Whetten, 2002) have demonstrated that employees with a high level of organizational identification exhibit affirmative behaviors and attitudes towards their organizations. The extensive research into the concept of organizational identification can be explained by the positive effect it has been shown to have on attitudes including job satisfaction, performance, motivation, employee retention and communication (Scott, Corman, & Cheney, 1998). Briefly, organizational identification may be defined as "the perception of oneness with or belongingness to an organization, where the individual defines him/herself in terms of the organization(s) of which he or she is a member" (Mael & Ashforth, www.ccsenet.org/ijbm International Journal of Business and Management Vol.…”
Section: Transformational Leadership Job Autonomy and Organizationalmentioning
confidence: 99%